2020
DOI: 10.1161/strokeaha.120.030898
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion Therapy Frequency and Outcomes in Mild Ischemic Stroke in the United States

Abstract: Background and Purpose: More than half of patients with acute ischemic stroke have minor neurological deficits; however, the frequency and outcomes of reperfusion therapy in regular practice has not been well-delineated. Methods: Analysis of US National Inpatient Sample of hospitalizations with acute ischemic stroke and mild deficits (National Institute of Health Stroke Scale [NIHSS] score0–5) from October 1, 2016, to December 31, 2017. Patient-and hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 21 publications
4
44
3
Order By: Relevance
“…Patients requiring intravenous thrombolysis and emergency revascularization were excluded from the present study; thus, many patients with potentially disabling stroke and large vessel stenosis or occlusion were excluded. Data from the United States showed that more than one-half of acute ischemic stroke hospitalizations had minor deficits, accounting for 4 of every 10 intravenous thrombolysis therapy (IVT) and 1 of every 10 mechanical thrombectomy treatments ( 18 ). A nationwide study in the United States, the excellent functional outcome only occurred in 48.2% of all minor strokes who underwent IVT or endovascular therapy (EVT) ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients requiring intravenous thrombolysis and emergency revascularization were excluded from the present study; thus, many patients with potentially disabling stroke and large vessel stenosis or occlusion were excluded. Data from the United States showed that more than one-half of acute ischemic stroke hospitalizations had minor deficits, accounting for 4 of every 10 intravenous thrombolysis therapy (IVT) and 1 of every 10 mechanical thrombectomy treatments ( 18 ). A nationwide study in the United States, the excellent functional outcome only occurred in 48.2% of all minor strokes who underwent IVT or endovascular therapy (EVT) ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the United States showed that more than one-half of acute ischemic stroke hospitalizations had minor deficits, accounting for 4 of every 10 intravenous thrombolysis therapy (IVT) and 1 of every 10 mechanical thrombectomy treatments ( 18 ). A nationwide study in the United States, the excellent functional outcome only occurred in 48.2% of all minor strokes who underwent IVT or endovascular therapy (EVT) ( 18 ). The exclusion of EVT and IVT minor ischemic stroke or TIA patients from the present study might contribute to the substantial-high proportion of favorable functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are geographic variations in IVT and EVT rates, with less than 8% to 10% and 2% IVT and EVT rates, respectively 6,7 . However, in optimized settings or some countries including—but not limited to—Austria, Denmark, the Netherlands, and United States; IVT and EVT rates of more than 10 and 3%, respectively, have been reported 6,8 . Furthermore, the outcomes of these treatments are highly time‐dependent, it is estimated every minute delay after stroke in an untreated patient leads to a loss of 1.9 million neurons, 9 and it has been observed that neurologic improvement and good functional outcome is associated with shorter time to reperfusion treatment 10 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, in optimized settings or some countries including-but not limited to-Austria, Denmark, the Netherlands, and United States; IVT and EVT rates of more than 10 and 3%, respectively, have been reported. 6,8 Furthermore, the outcomes of these treatments are highly time-dependent, it is estimated every minute delay after stroke in an untreated patient leads to a loss of 1.9 million neurons, 9 and it has been observed that neurologic improvement and good functional outcome is associated with shorter time to reperfusion treatment. 10 Thus, improvements to time delay to stroke treatment for AIS patients is essential because it can improve the number of patients treated with reperfusion therapy and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that more than one-half of acute ischemic stroke (AIS) hospitalizations had mild deficits, accounting for four of every 10 patients who received intravenous thrombolysis (IVT) therapy in national US practice [ 1 ]. Despite only initial mild neurological symptoms, nearly a third of patients with minor stroke not receiving alteplase treatment suffered functional disability at 90-day post stroke [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%